2013
DOI: 10.2172/1097164
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Some Physical Properties of Zirconium Alloys for Nuclear Applications in Support of UFD Campaign

Abstract: Zirconium-based alloys Zircaloy-2 and Zircaloy-4 are widely used in the nuclear industry as cladding materials for light water reactor (LWR) fuels. These materials display a very good combination of properties such as low neutron absorption, creep behavior, stress-corrosion cracking resistance, reduced hydrogen uptake, corrosion and/or oxidation, especially in the case of Zircaloy-4. However, over the last couple of years, in the post-Fukushima Daiichi world, energetic efforts have been undertaken to improve f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 76 publications
(96 reference statements)
3
5
0
Order By: Relevance
“…In Table 5, the values of the lattice parameter of each cell vary little from one hydride to another. Our results agree very well with the calculations made by Glazoff [41] and with the available experimental data. The hydride formation enthalpy, E x f , is calculated as Glasoff [41].…”
Section: Zirconium Hydridessupporting
confidence: 92%
See 2 more Smart Citations
“…In Table 5, the values of the lattice parameter of each cell vary little from one hydride to another. Our results agree very well with the calculations made by Glazoff [41] and with the available experimental data. The hydride formation enthalpy, E x f , is calculated as Glasoff [41].…”
Section: Zirconium Hydridessupporting
confidence: 92%
“…Our results agree very well with the calculations made by Glazoff [41] and with the available experimental data. The hydride formation enthalpy, E x f , is calculated as Glasoff [41].…”
Section: Zirconium Hydridessupporting
confidence: 92%
See 1 more Smart Citation
“…In this system in particular, it has been found that H preferentially occupies tetrahedral sites in the Zr lattice, rather than other sites 15,21,22 . Some works have focused on the octahedral site as the main location for H atom solution, however such works appear to be in the minority 23,24 . It has been theoretically predicted that the FCT structure of ZrH 2 can have another stable phase for c/a ¿ 1 25,36 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Since cadmium has a high neutron absorption cross section and also causes stress corrosion cracking in these alloys, the maximum allowed limit of cadmium in these alloys is restricted to 0.5 mg g À1 for nuclear applications. These materials exhibit a very good combination of properties such as low neutron absorption, high creep resistance, stress-corrosion cracking resistance, reduced hydrogen uptake, corrosion and/or oxidation resistance, especially in the case of Zircaloy-4.…”
Section: Introductionmentioning
confidence: 99%